Using the constructal law to predict climate changes versus atmospheric properties - Meunier, F. (2011)
A simple and transparent model, based on the constructal law, is used to study climate change as a response to changes in atmospheric properties (albedo-- and greenhouse factor –-). This model is first used to study the climate response to present changes in albedo and greenhouse factor. This allows comparing, in terms of energy imbalance and temperature, the climate change observed between 1880 and 2003 and that given by the model. Then, the model is used to predict future climate changes depending on several scenarios for the increase of atmospheric properties. This approach proves that the constructal law can help in defining new scenarios in relation to carbon emission policies. As an example, two scenarios are therefore tested and it is shown that the 2K critical temperature increase can be avoided only if a global low carbon energy pathway strategy is decided well before 2060.